ANALISIS PENYETORAN, PELAPORAN, DAN PENCATATAN PPH FINAL PASAL 4 AYAT (2) ATAS BUNGA DEPOSITO DAN TABUNGAN NASABAH PADA BPR PRISMA DANA CABANG AMURANG - Muhea, Marchella Tiara; Tinangon, Jantje J.; Elim, Inggriani (Universitas Sam Ratulangi, 2016)
The income tax is the largest source of income in taxes. The income tax is a tax impossed on the income received by the taxpayer in the tax year. One type of income tax is the Final Income Tax Article 4 Paragraph 2 on interest deposit and customer’s savings. The purpose of this research was to determine the suitability of depositing, reporting, and recordkeeping Final Income Tax Article 4 (2) on interest deposits and savings at BPR Prisma Dana, branch Amurang with tax regulations. The method used in this research is descriptive analysis. The results of this study indicates that BPR Prisma Dana, branch Amurang already done the tax obligation in cutting, depositing, and report final income tax article 4 paragraph 2 on deposit and saving account, but there is a delay in depositing and reporting taxation. Instead, the payment and reporting can be done on time, so as not to incur administrative fines. Keywords: payment, reporting, interest on deposits, savings